1996
DOI: 10.4319/lo.1996.41.3.0396
|View full text |Cite
|
Sign up to set email alerts
|

Controls on iron(III) hydroxide solubility in seawater: The influence of pH and natural organic chelators

Abstract: Iron solubilities of Fe(III) hydroxide in coastal and oceanic waters and in the ultraviolet (UV)-irradiated seawaters over a pH range of 5.7-8.2 at 20°C were determined by a sim:Dle filtration (0.025 pm) involving y-activity measurement of 59Fe. At pH ranges of 5.7-7.2 (coastal water) and of 5.7-7.6 (oceanic water), only the Fe(OH),+ species is significant. The calculated solubility products, log*&,, for coastal and oceanic waters were 4.8-5.0 and 4.4-4.6, respectively. The solubilities within the pH range of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
288
1
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 306 publications
(298 citation statements)
references
References 39 publications
8
288
1
1
Order By: Relevance
“…At pH>6, Fe(III) is chiefly in the insoluble Fe(OH) 3 (ferrihydrite) form, so that the photo-degradation process could occur at the water/solid interface (Calza, et al 2005) as already observed in seawater (Byrne, and Kester, 1976, Kuma, et al 1992and 1996; 2) stirred (for 96h) or unstirred solutions, in order to evaluate if the equilibrium among the different species is easily (or not) reached.…”
Section: Fe(ii)/fe(iii)mentioning
confidence: 99%
“…At pH>6, Fe(III) is chiefly in the insoluble Fe(OH) 3 (ferrihydrite) form, so that the photo-degradation process could occur at the water/solid interface (Calza, et al 2005) as already observed in seawater (Byrne, and Kester, 1976, Kuma, et al 1992and 1996; 2) stirred (for 96h) or unstirred solutions, in order to evaluate if the equilibrium among the different species is easily (or not) reached.…”
Section: Fe(ii)/fe(iii)mentioning
confidence: 99%
“…[46,47] A considerable body of work, particularly by Kuma and associates, on the solubility of Fe III in seawater points towards the important role of natural organic matter in controlling the solubility of iron in surface and deep waters by forming complexes with Fe III , and the potential generation of ligands from oxidation of organic material in deep waters. [48][49][50][51][52][53][54][55] In addition, several direct measurements of the complexation of Fe III by organic matter in seawater have been reported, mainly as a result of electrochemical titration measurements. These measurement methods and results have been recently reviewed by Bruland and Rue.…”
Section: Iron In Seawatermentioning
confidence: 99%
“…The reduced Fe(II), although more soluble in seawater, becomes rapidly oxidized by O 2 and H 2 O 2 (King et al, 1995;Millero and Sotolongo, 1989;Millero et al, 1987). Iron solubility is significantly increased by the strong chelation of Fe in the dissolved fraction (b 0.2 µm) by organic or inorganic Fe-binding (Boyé et al, 2005;Kuma et al, 1996). These Fe-binding ligands are often found in excess over the DFe pool (Boyé et al, 2001).…”
Section: Introductionmentioning
confidence: 99%